Recent insights into the biological roles of mucin-type O-glycosylation - Tian, E (2008)
In this special issue of the Glycoconjugate Journal focusing on glycosciences and development, we summarize recent advances in our understanding of the role of mucin-type O-glycans in development and disease. The presence of this widespread protein modification has been known for decades, yet identification of its biological functions has been hampered by the redundancy and complexity of the enzyme family controlling the initiation of O-glycosylation, as well as the diversity of extensions of the core sugar. Recent studies in organisms as diverse as mammals and Drosophila have yielded insights into the function of this highly abundant and evolutionarily-conserved protein modification. Gaining an understanding of mucin-type O-glycans in these diverse systems will elucidate crucial conserved processes underlying many aspects of development and homeostasis.